Learning outcomes improvement in primary and lower secondary education: a systematic review of education reform policies on a state-level case in Brazil - Takeuti, Adriana Mitiko do Nascimento (Frontiers in Education, 2026)
This study examines the education reform implemented in the State of Ceara, Brazil, which has achieved notable improvements in learning outcomes, mainly in primary and lower secondary education, despite persistent socioeconomic constraints. The research aims to identify the policies that explain the continuity and effectiveness of the Ceara reform over time. A qualitative approach was employed, following the PRISMA 2020 reporting guidelines. The review was guided by two research questions: (1) How can academic studies on learning improvements in Ceara be characterized; and (2) Which components of Ceara’s education policies are associated with reported improvements in learning outcomes. Eighty studies published between 2005 and 2024 were selected from academic databases and coded to identify policy instruments, governance arrangements, and implementation dynamics associated with improved learning outcomes. The findings reveal that Ceara’s education model emerged from the convergence of coherent governance, performance-based financing, and sustained teacher training that reinforced one another over time. The reform was marked by institutional continuity, strong collaboration between state and municipal governments, and the use of assessments, as well as incentives to guide decision-making. However, the review also highlights risks associated with competitive funding and test-driven accountability, including exclusionary practices and a limited focus on measurable learning dimensions. Overall, the analysis demonstrates that Ceara’s education reform exemplifies how multi-level policy coherence and long-term institutional commitment can yield measurable learning outcomes, while also highlighting the importance of striking a balance between efficiency, inclusion, and educational equity.